Family Album: the people who make up 20 years of Information Design research in Pernambuco - Ranoya, Guilherme; Rolim Miranda, Eva; Galvão Coutinho, Solange (InfoDesign, 2024)
This article presents the comprehensive trajectory undertaken to map the Information Design researchers trained in the Postgraduate Program in Design at UFPE, identifying and categorizing their research, the period in which it was conducted, their advisors, their themes, that is, the entire production of ID in the region, and the people involved in it. The problem originates from the construction of the memory of how Information Design developed in the northeast of Brazil, and the difficulty encountered in accurately presenting simple quantitative data. We report here the process and strategies applied to carry out this survey. The mapping, which continues, leads to an interactive memory artifact, which contributes in a subtle but relevant way to ID research: a “family album”, which establishes a sense of community. Perhaps the most significant contribution of this work lies in demonstrating that memory and the sense of belonging are part of the research support infrastructure, operating on delicate and often overlooked aspects of scientific production, such as the motivation and emotional well-being of researchers.